Understanding and improving cold bituminous emulsion mixtures - Saadoon, Tahseen Diwan (2019)
Cold Asphalt Mixture (CAM) is a pavement material usually produced by mixing bitumen emulsion, aggregate, water, and cement at ambient temperature. CAM has many economic, environmental, energy-saving, and health and safety advantages compared to other types of mixtures used in roads, but it has weak mechanical performance as a structural layer, mainly due to containing trapped water. Consequently, studies attempting to increase the mechanical performance of CAM have attempted to dispose of its water content by promoting suction, absorption and consumption of water using cementitious and/or pozzolanic materials. Despite numerous attempts, CAM still has weak final performance, characterised by high porosity and slow development of performance in comparison to Hot Mix Asphalt (HMA). This is due to the lack of a deeper understanding of the dynamics of water evaporation, moisture and temperature profiles in CAM. Therefore, this research aims to investigate, understand and predict: the dynamics of water evaporation and the mechanical performance of CAM (with and without cement); and the affects of CAM components on performance (curing and strength).